ANALISIS PENGUKURAN KOMPETENSI PENDIDIKAN PROFESI GURU DALAM JABATAN - Asep Wijaya; Muhammad Wali Ismady; Rosdiana (LPPM IAI Almuslim Aceh, 2024)
Good education is a key factor in the development of a country's society and economy. The teaching profession has a central role in providing quality education to the younger generation, preparing them to face future challenges through the teacher professional education program (PPG). This research aims to analyze more deeply regarding assessment or measurement in the teacher professional education program (PPG), especially for those in position. The research method uses a literature review with data sources in the form of books and journal articles and continues using content analysis techniques at the end with the validity of the data using a credibility test using a check and recheck system. The results of the discussion show that assessing or measuring PPGDJ students can be carried out using the material deepening stage, workshops, field experience practice, knowledge test, and finally performance test. There are four teacher competencies in law, namely pedagogical competence, personal competence, professional competence, and social competence.